REAR SUSPENSION DAMPER SUPPORT VIRTUAL DURABILITY AND LOAD RECONSTRUCTION - Coutinho, Ismael; Landre Jr., Jánes; Magalhães, Pedro A.; Caiafa, Maxwell; Toledo, Marcelo (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Reliability is essential at commercial vehicles development: crucial for brand reputation and to avoid financial losses due to inoperative machinery. Vehicle suspension purpose is absorbing track roughness and ensure a comfortable and safe ride. The damper is an essential component of this system and its support must withstand typical loads, especially impacts, since the efforts are proportional to event velocity. The aim of this work is predict rear damper support life at one durability missions of product’s validation plan: Rough Road. The loads histories are crucial for reliable durability result and were reconstructed from strain measurements at strategic point, optimized to assure correlation between virtual and experimental results.